25. STATUS OF METHADONE SUBSTITUTE MANAGEMENT AND TREATMENT FOR DRUG ADDICTS IN HA DONG FACILITY, HANOI IN 2023 (Vietnam Journal of Community Medicine, 2023)
Objective: Describe the current status of Methadone replacement therapy in opiate addicts. Research subjects and methods: Cross-sectional descriptive study based on retrospective 230 medical records of all addicts undergoing Methadone treatment at Ha Dong facility in 2023. Results: The rate of drug addicts’ information being assessed daily during dosing was 99.6%. Most drug addicts probe for 3 weeks before adjusting the dose (99.6%). Most drug addicts received an increase of 10 mg when adjusting (99.1%). The rate of toxicity assessed when adjusting the dose was only 71.7%. The proportion of people whose urine was monitored monthly is 63.5%, and less than once a month is 36.1%. Most drug addicts have been evaluated and monitored correctly according to the instructions, 98.3%. The rate of side effects evaluated and treated according to instructions is 99%. Drug addicts miss the highest dose during the initiation phase (46.1%) and adjustment phase (38.3%). All cases of missed doses were handled correctly. Conclusion: Opiate replacement treatment with Methadone has been implemented very well according to regulations at Ha Dong Methadone Treatment Center. However, regular assessment of the addict during the titration and dosage phase should be done with more caution when increasing the dose.
Keywords: Methadone, substitution treatment, opioids, treatment adherence, treatment management.